Training Syntax to Enhance Theory of Mind in Children with ASD. - Durrleman, Stephanie; Bentea, Anamaria; Prisecaru, Andreea; Thommen, Evelyne; Delage, Hélène (Journal of Autism & Developmental Disorders, 2023)
Preschool children with neurotypical development (ND) trained on sentential complements ("X thinks/says that") improve their Theory of Mind (ToM) performance. Can complementation training also enhance ToM in children with Autism Spectrum Disorder (ASD)? Thirty-three children with ASD (Mage = 8;11) and 20 younger ND peers (Mage = 4;3) were trained on sentential complements (4–6 weeks, 2–3 times per week, via the DIRE i-Pad App). Pre-training and post-training comparisons show that (1) training boosted both complementation and ToM performance across groups; (2) improvements remained 4–6 weeks after training ended; (3) participants with milder ASD symptoms made most gains. Training on sentential complements thus seems beneficial for addressing ToM difficulties in children with ASD, especially those with milder symptoms.